El papel del patologo, entomologo y otros en adicion del mejorador. Importancia de trabajar en equipo - Pastor Corrales, Marcial A. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
The advantages of a multidisciplinary team approach in bean improvement programs to study the different aspects (biological, climatic, and edaphic) affecting production are indicated. The activities of each specialist complement those of the other members, thus increasing working efficiency. However, the administrative structure existing at several institutions hinders the development of a coordinated work team that integrates the different specialists. CIAT's contribution regarding the training of personnel in this area at the different national institutions is recommended. (CIAT)